2017
DOI: 10.1113/jp273408
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ischaemic mitochondrial substrate constraint by inhibition of malate‐aspartate shuttle preserves mitochondrial function after ischaemia–reperfusion

Abstract: Mitochondrial dysfunction plays a central role in ischaemia-reperfusion (IR) injury. Pre-ischaemic administration of aminooxyacetate (AOA), an inhibitor of the malate-aspartate shuttle (MAS), provides cardioprotection against IR injury, although the underlying mechanism remains unknown. We hypothesized that a transient inhibition of the MAS during ischaemia and early reperfusion could preserve mitochondrial function at later phase of reperfusion in the IR-injured heart to the same extent as ischaemic precondit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 37 publications
(50 reference statements)
1
50
0
Order By: Relevance
“…Mitochondrial respiratory function was analyzed in duplicate at 37 • C using a two-chamber high-resolution respirometer (Oroboros Instruments, Innsbruck, Austria), as previously described [21,22]. Sequential titrations of substrates and inhibitors were performed in the following order and concentrations: (i) Glutamate (10 mmol L −1 ) and malate (2 mmol L −1 ) to assess state 2 leak respiration; (ii) ADP (5 mmol L −1 ) to assess state 3 respiration with complex I substrates; (iii) cytochrome c (10 µmol L −1 ) to assess the integrity of the outer mitochondrial membrane with an increase in respiration of >10% considered as a sign of damage leading to elimination of data; (iv) succinate (10 mmol L −1 ) to assess state 3 respiration with complex I and II substrates; (v) oligomycin (2 µg mL −1 ) to assess state 4 respiration; (vi) rotenone (0.5 µmol L −1 ) and antimycin A (2.5 mmol L −1 ) to asses residual oxygen consumption.…”
Section: High-resolution Respirometrymentioning
confidence: 99%
“…Mitochondrial respiratory function was analyzed in duplicate at 37 • C using a two-chamber high-resolution respirometer (Oroboros Instruments, Innsbruck, Austria), as previously described [21,22]. Sequential titrations of substrates and inhibitors were performed in the following order and concentrations: (i) Glutamate (10 mmol L −1 ) and malate (2 mmol L −1 ) to assess state 2 leak respiration; (ii) ADP (5 mmol L −1 ) to assess state 3 respiration with complex I substrates; (iii) cytochrome c (10 µmol L −1 ) to assess the integrity of the outer mitochondrial membrane with an increase in respiration of >10% considered as a sign of damage leading to elimination of data; (iv) succinate (10 mmol L −1 ) to assess state 3 respiration with complex I and II substrates; (v) oligomycin (2 µg mL −1 ) to assess state 4 respiration; (vi) rotenone (0.5 µmol L −1 ) and antimycin A (2.5 mmol L −1 ) to asses residual oxygen consumption.…”
Section: High-resolution Respirometrymentioning
confidence: 99%
“…For example, a recent study by Jespersen and colleagues showed pre‐ischaemic administration of AOAA reduced infarct size and protected the heart against ischaemia‐reperfusion injury. And, the authors owed its cardioprotection to the inhibiting of malate‐aspartate shuttle . Therefore, it is warranted to further investigate the cardioprotective mechanisms of AOAA using specific inhibitors of different enzymes separately.…”
Section: Discussionmentioning
confidence: 99%
“…And, the authors owed its cardioprotection to the inhibiting of malate-aspartate shuttle. 46 Therefore, it is warranted to further investigate the cardioprotective mechanisms of AOAA using specific inhibitors of different enzymes separately.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial respiration was measured with high-resolution respirometry (Oroboros, Innsbruck, Austria) in permeabilized cardiac muscle fibers as previously described [5]. In short, two titration protocols were used to evaluate glucose and fatty acid linked respiration: Protocol 1 (complex I+II-linked respiration): State 2 respiration (GM) was assessed with malate (2 mM) and glutamate (10 mM).…”
Section: Methodsmentioning
confidence: 99%